GLYCAEMIC OUTCOMES FOLLOWING INSULIN DE-INTENSIFICATION IN PATIENTS WITH TYPE 2 DIABETES MELLITUS: A RETROSPECTIVE OBSERVATIONAL STUDY IN A MALAYSIAN TERTIARY CENTRE - Nasir, Nur Hafizah Mohamad; Yusoff, Yusniza; Hidzir, Sarina Anim Mohd (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION Insulin deintensification is the reduction, simplification, or cessation of insulin therapy. Despite its potential benefits, there is limited local data on real-world insulin deintensification practices. We investigated the impact of insulin deintensification on glycemic control among patients with type 2 diabetes mellitus (T2DM) attending outpatient follow-up at a Malaysian tertiary hospital. METHODOLOGY We conducted a retrospective observational study at the outpatient clinic of Hospital Sungai Buloh from January to December 2024. Adults with T2DM who underwent insulin deintensification were included. Patients with type 1 diabetes, gestational diabetes, or incomplete follow-up data were excluded. Primary outcomes were changes in HbA1c and pre-breakfast blood glucose (BG) levels. Secondary outcomes examined associations between diabetes duration and baseline HbA1c with glycemic outcomes. Paired t-tests and correlation coefficient tests were used for statistical analyses. RESULT A total of 33 patients were included. Most (n = 22) were initially on a basal-bolus regimen and subsequently de-intensified to premixed human insulin (n = 12), premixed analogue insulin (n = 7), oral agents (n = 2), or basal-only insulin (n = 1). Among nine patients initially on human premixed insulin, five were switched to a premixed analogue regimen, two to oral agents, one to basal-only insulin, and one to basal analogue. Of the two patients on basal insulin, one transitioned to oral agents and the other to a premixed analogue regimen. Nineteen patients had complete paired HbA1c data, with mean HbA1c improving from 10.36% (SD 2.70) to 8.93% (SD 2.49) (mean change −1.43%, p = 0.003). Fifteen patients had complete pre-breakfast BG data, showing a mean reduction from 12.07 mmol/L (SD 3.86) to 9.90 mmol/L (SD 3.22) (p = 0.037). Baseline HbA1c strongly correlated with follow-up HbA1c (r = 0.76, p <0.001). Meanwhile, diabetes duration showed no significant association (r = −0.24, p = 0.365). CONCLUSION Insulin deintensification was associated with significant improvements in HbA1c and pre-breakfast BG levels, supporting its safe implementation in selected patients with T2DM. Baseline HbA1c was a strong predictor of post-intervention control. These findings highlight the potential for regimen simplification with structured follow-up and monitoring.